Sinergi pemberdayaan petani melalui penataan kelembagaan inklusi dan pengolahan limbah ramah lingkungan di Sialang Palas, Siak - Khairul Anwar; Adiwirman Adiwirman; Adianto Adianto; Syofian Hadi (Unri Conference Series: Community Engagement, 2022)
This service activity is in partnership with the Palm Oil Farmer Group (Poktan) of Lubuk Dalam- Siak District. These Poktan partners face problems, namely how to empower Poktan Karya Bersama in order to increase productivity through institutional synergy relationships? In answering partner problems, this service activity offers marketing-based inclusion group management solutions and improves processing skills. The purpose of this activity is to utilize cow-palm waste into compost; (2) Increase knowledge in reorganizing inclusion management in the Joint Works Farmer Group. As for the method: First, Socialization of activities and FGD. Second, establishing a working group (Pokja) as a means of building synergistic inclusion; Lectures and discussions. Third, the management of palm oil waste, cows into compost (3) Perform the Simulation stage. Fourth, assistance to palm oil poktan farmers by the service team in collaboration with PPL and village government officials Through this service activity is expected to provide benefits in increasing production and marketing of Poktan Karya Bersama's results in the future. The results of this activity have an impact on increasing the knowledge and proficiency of farmers as well as farmers' income patterns. The enthusiasm of the participants in lectures, exercises and simulations was quite high with indicators of the number of questions asked, the extension of the session time and the desire of the participants for this activity to be carried out again.